A Generalized Bilateral Trading Model - Tao, Rongchuan (Scientific Research, 2018)
In the bilateral trading model developed by Myerson [1], an ex post efficient mechanism that satisfies incentive compatibility and individual rationality has been proved to be not existed. This paper is aimed at the discussion of modified bilateral trading model where the buyer and seller’s valuations for the object are assumed to be not independent. Under such assumption, we concern about the existence of an ex post efficient mechanism satisfying individual compatible and individual rational conditions. We will give a necessary condition of such mechanism, not precisely though, to identify the existence. At the end of this paper, we provide some empirical evidences about the non-independent assumption and suggest some directions for further research, both empirical and theoretical.
Keywords: Bilateral Trading; Mechanism Design; Individual Rationality; Incentive Compatibility; Ex Post Efficient; Generalized Model